“Beyond jihad”: The Islamic contributions to the field of strategic studies - Oyosoro, Felix Idongesit (Penerbit Universiti Kebangsaan Malaysia, 2023)
Several historical literatures in the field of Strategic Studies (Gray, 2013; Heuser, 2010; Kane, 2013) have always centered its Hellenic and ancient Oriental origins, ignoring (or negating) the contributions of other cultures (African, Islamic, etc.) to the discipline. Furthermore, in the modern era, references to the Islamic strategy of warfare have been reduced to one of its components: Jihad (Bar 2008, Zabel 2007, Spencer 2019). This is due, in part, to the recent theology of Islamic militants (Al Qaeda, for example), who have portrayed (erroneously) Jihad as the sole strategy of Islamic warfare in contemporary times. As a result, this research highlights the contributions of Islamic thoughts on Peace and Warfare. This paper aims to highlight major Islamic scientific thoughts on warfare through a historical attempt. The goal of this exercise is to correct two errors: first, to reintroduce Islamic perspectives on peace and warfare into the canon of Strategic Studies, and second, to correct the contemporary perception of Islamic warfare contributions as primarily jihadist in nature. This study employs comparative historical research methodology to describe the vast literature of Islamic strategic thoughts and events in order to demonstrate the historical shortcomings of the west's rejection or ignorance of Islam's contributions to the field of strategic thinking.